LEGAL CERTAINTY OF LAND TITLE IN FACILITATING FOREIGN DIRECT INVESTMENT IN ACEH PROVINCE, INDONESIA - Dina Luqyana; Azhari Yahya (Student Journal of International Law, 2021)
Law Number 25 Year 2007 on Capital Investment facilitates services and/or licensing of Land Rights to Use for investment. Article 22(a) stipulated that land Rights to Use (HGB) can be granted up to 95 years for land cultivation rights, up to 160 years for building use rights, and up to 140 years for land Rights to Use. However, land Rights to Use regulated in Qanun Number 14 Year 2017 on Aceh's Assets Management is only five years subject to certain conditions and requirements for extension. It is clear that there two legislations available in Aceh in terms of facilitating land license for investment. Therefore, a research question raised is which law is applied by the Government of Aceh to speed the process of land license for the investor? This study uses normative legal research by relying on primary and secondary legal resources. Primary legal resources were collected by analyzing related legislations, while secondary legal resources were obtained by reviewing associated literature. The result shows that in facilitating land license for investors in Aceh, the Government of Aceh applies Qanun Number 14 Year 2017 on Aceh's Assets Management instead of Law Number 25 Year 2007 on Capital Investment. This Qanun stipulated that land license for investors is given for five years with specific requirements for extension. This short period for a land license causes legal uncertainty for investors and decreases their motivation to invest in Aceh Province. It is suggested that this Qanun should be amended to be in line with national legislation, namely law Number 25 Year 2007 that provides a longer period of land license for investors. Keywords: Legal certainty; Land license; Foreign Direct Investment.